Deteksi Lintasan Gerak Tangan Berbasis Pengolahan Citra Menggunakan Metode K-Means - Isnawati, Nurvia; Himamunanto, AR.; Budiati, Heani (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Technological developments have demanded continuous research so that it becomes more advanced in bringing benefits to computer science in particular. As is known, hand gestures are often used to convey meaning and can be used to interact with computers. Research by building software using Matlab R2020a which processes video input using a method approach based on image processing. The aim of the method approach in this research is to compute the coordinates of hand gesture objects to obtain hand movement trajectories. The research results of the K-Means method which was implemented to describe trajectory patterns can process the quality of segmented objects with exposure to dim light. The quality of segmentation that obtains the correct area of the hand gesture object influences the K-Means method in presenting trajectories in describing hand movement action patterns. The K-Means method can describe the trajectory of hand movements on the quality of segmented objects with dim light exposure. The longer the duration, the longer the processing will take, with the reality found that object detection processing based on image processing still takes longer than video viewing. With the hope that precise trajectories with hand movements can be understood as patterns in conveying meaning.